Biochemistry Characterization of Inhibin from Goat Granulosa Cells - Siregar, TN; Aulanni’am, Aulanni’am; Susilawati, T; Riady, G; Hamdan, Hamdan; Armansyah, T (ANIMAL PRODUCTION, 2006)
The objective this research is to study the isolation and characterization of inhibin from goat granulosa cells. Sample of ovary collected from abbatoir of Sukun in Malang. Minimum diameter of follicle that can be used in this research is 3 mm. Granulosa cells Oocytes collection was done by aspiration method, and granulosa cells separate from oosit mechanically. Biochemistry characterization of inhibin was done by technique of SDS PAGE, biuret and PAS. The result of research confirmed that inhibin has molecular 32 kDa. Composition of protein, carbohydrate, and glikoprotein inhibin was 3.636±0,002; 2.569±0,002; and 6.205±0.016 mg/mL, respectively. (Animal Production 8(2): 100-107 (2006) Key Words: Inhibin, granulosa cells, oocytes, follicle